Implementation of Virtual Learning Objects in the Development of Mathematical Skills: A Qualitative Analysis from the Student Experience - Cóndor-Herrera, Omar (2021)
This article reports a research of a qualitative methodology that analyzed narratives of students aged between 10 and 14 years old, who received a learning technological program based on Virtual Learning Objects. As results, it was found that the program applied propitiate significant willingness, happiness, motivation, and innovation towards learning mathematics. There is discussed about the need of the implementation of this methodology in benefit of learning mathematics.